(3TQM GdYbhO GdOQjI aj GdCeQGA GdeUQjIs - (3eMeO Hf GdXQjas; (3GHf GdLRGQ , Ydj Hf GdLRGQ GdeUQj GdMfaj, fhQ GdOjf CHh GdMSf,J (B984 (3g` s ((3GdeDda s)
(3ChdgG (B:s
(3hHYO abO hbaJ ddTjN CHj GdMSjfi Hf GdLRGQ hUd ajgG Edi Ohdg Gdedc GdSYjO Ke Jhai s
(3TQM ajg CQLhRI CHj GdMSf Hf GdLRGQs
(3hQOJ CjVkG eY JGL GdeYGQa hJGQjN GdNdGFb JMJ Qbe (B944 (3JGQjNs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B51s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B191 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs